Intelligent computing, communication and devices : proceedings of ICCD 2014, Volume 1 - Jain, Lakhmi C.; Patnaik, Srikanta; Ichalkaranje, Nikhil (Advances in Intelligent Systems and Computing, 2015)
In the history of mankind, three revolutions which impact the human life are tool-making revolution, agricultural revolution and industrial revolution. They have transformed not only the economy and civilization but the overall development of the human society. Probably, intelligence revolution is the next revolution, which the society will perceive in the next 10 years. ICCD-2014 covers all dimensions of intelligent sciences, i.e. Intelligent Computing, Intelligent Communication and Intelligent Devices. This volume covers contributions from Intelligent Computing, areas such as Intelligent and Distributed Computing, Intelligent Grid & Cloud Computing, Internet of Things, Soft Computing and Engineering Applications, Data Mining and Knowledge discovery, Semantic and Web Technology, and Bio-Informatics. This volume also covers paper from Intelligent Device areas such as Embedded Systems, RFID, VLSI Design & Electronic Devices, Analog and Mixed-Signal IC Design and Testing, Solar Cells and Photonics, Nano Devices, and Intelligent Robotics.